Effects of ultrasound-guided lumbar-sciatic nerve block and epidural anesthesia on the levels of IL-6, IL-8, TNF-α and coagulation factors in peripheral blood of elderly patients after hip joint surgery - Huang, Zhi; Cai, Yan; Yang, Yunfei; Shi, Jin; Zhao, Xuya; Mo, Haise; Zeng, Qingfan (Journal of Medical Biochemistry, 2022)
Objective: To investigate the effects of different anesthesia methods on the levels of inflammatory and coagulation factors in the peripheral blood of elderly patients undergoing hip surgery.Methods: 144 elderly patients undergoing hip arthroplasty in our hospital were randomly divided into ultrasound-guided lumbar-sciatic nerve block (group A) and epidural anesthesia (group B), 72 cases in each group. The postoperative hemodynamic indexes, pain score, inflammatory factors and coagulation factor levels were compared between the two groups.Results: (1) The postoperative VAS score of group B patients was lower than that of group A (P
Keywords: lumbar slave-sciatic nerve block; epidural anesthesia; inflammatory factor; coagulation factor